The Anti-Adhesive Effect of Curcumin on Candida albicans Biofilms on Denture Materials - Alalwan, Hasanain; Rajendran, Ranjith; Lappin, David F.; Combet, Emilie; Shahzad, Muhammad; Robertson, Douglas; Nile, Christopher J.; Williams, Craig; Ramage, Gordon (Frontiers in Microbiology, 2017)
The use of natural compounds as an alternative source of antimicrobials has become a necessity given the growing concern over global antimicrobial resistance. Polyphenols, found in various edible plants, offers one potential solution to this. We aimed to investigate the possibility of using curcumin within the context of oral health as a way of inhibiting and preventing the harmful development of Candida albicans biofilms. We undertook a series of adsorption experiments with varying concentrations of curcumin, showing that 50 ug/ml could prevent adhesion. This effect could be further synergised by the curcumin pretreatment of yeast cells to obtain significantly greater inhibition (>90%, p<0.001). Investigation of the biological impact of curcumin showed that it preferentially affected immature morphological forms (yeast and germlings), and actively promoted aggregation of the cells. Transcriptional analyses showed that key adhesins were down-regulated (ALS1 and ALS3), whereas aggregation related genes (ALS5 and AAF1) were up-regulated. Collectively, these data demonstrated that curcumin elicits anti-adhesive effects and that induces transcription of genes integrally involved in the processes related to biofilm formation. Curcumin and associated polyphenols therefore have the capacity to be developed for use in oral healthcare to augment existing preventative strategies for candidal biofilms on the denture surface.